Domestic Wastewater Treatment by Root Zone Technology Option: Colacassia Plant - Poonam Thorat; Sayyad Saniya; Salman Shaikh; Raashida Shaikh; Atul Sonawane (International Journal of Engineering and Management Research, 2019)
Root Zone Technology is one of the low cost methods to treat wastewater. With the help of this system we can treat the Non-Point sources with best results. To achieve this goal we have to divide the Non-Point sources into constructed channels within the river bank followed by root zone bed or if the Non-Point Sources is coming from natural nallas we can provide this system within its Channel. We have prepared channel on which I have developed the root zone bed and have lab analysis of rector out put on number of parameters. Flow rate and Detention time are the two factors on which channels are to be designed. Therefore I am changing the flow rate and finding out the change in parameter with respect to detection time. The optimization is when we get best result with maximum flow. I have got satisfactory results for the detention time of Three day, Seven day and twenty one day and Three day. With the help of this data I have designed the root zone bed system for the selected actual Domestic Sources.